Networks of institutions : institutional emergence, social structure and national systems of policies - Dai, Shuanping (Abingdon, Oxon : Routledge, 2014)
'The questions such as,'why the focuses of national policies vary significantly across countries, although their sources of policies are to a great extent identical';'why national development experiences mostly cannot be transplanted successfully among countries';'why some ineffective institutions persist over long periods of time', have attracted numerous efforts. This book provides a new perspective and argues that the answers lie in the existence of the networks of institutions and thus of national systems of policies (NSP) within national frameworks.Institutions are the equilibria of games and exist as rules of games. Therefore, a basic setting is that institutions emerge endogenously from a series of social interactions, and the interacting human agents are connected and interdependent at the overlapping interaction platforms. National policies and developmental strategies can be modelled in this approach too. The networks of institutions describe the dynamic connected structure among institutions in the process of social interactions over time. Regarding the national policies response to the recent economic crises, this book argues that the difference comes from the distinct understandings of the tags of the policies, which highly depend on the distinct national contexts, such as national interests, cultural background, political systems and so forth.This book represents a significant contribution to the literature which will be essential reading for those interested in institutional economics, network theory, social structures and economic policy. In particular, the approach of applying network game theory in institutional emergence, and the terms developed, i.e. tags of institutions, and national systems of policies, in this book, are illuminating and deserve more attention'--
Includes bibliographical references and index.
Keywords: Policy sciences; Social structure; Social institutions